Data from complete mtDNA sequencing of Tunisian centenarians: testing haplogroup association and the "golden mean" to longevity - Costa, MD (2009)
Since the mitochondrial theory of ageing was proposed, mitochondrial DNA (mtDNA) diversity has been largely studied in old people, however complete genomes are still rare, being limited to Japanese and UK/US samples. In this work, we evaluated possible longevity associated polymorphisms/haplogroups in an African population, from Tunisia, by performing complete mtDNA sequencing. This population has a mixed Eurasian/sub-Saharan mtDNA gene pool, which could potentially facilitate the evaluation of association for sub-Saharan lineages. Sub-Saharan haplogroups were shown to be significantly less represented in centenarians (9.5%) than in controls (54.5%), but it is not possible to rule out an influence of population structure, which is high in these populations. No recurrent polymorphism were more frequent in centenarians than in controls, and although the Tunisian centenarians presented less synonymous and replacement polymorphisms than controls, this difference was not statistically significant. So far, it does not seem that centenarians have significantly less mildly deleterious substitutions, not only in Tunisia but also in Japanese and UK/US samples, as tested here, not favouring a "golden mean" to longevity.